2022
DOI: 10.1136/jnnp-2022-329389
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Parkinson’s disease in multiple sclerosis and neuromyelitis optica spectrum disorder: a nationwide cohort study in South Korea

Abstract: BackgroundNeurodegeneration is associated with pathogenesis of both multiple sclerosis (MS) and neuromyelitis optica (NMOSD). Parkinson’s disease (PD) is a representative neurodegenerative disease, however, whether MS or NMOSD is associated with risk of PD is not known.MethodsMS and NMOSD cohorts were collected from the Korean National Health Insurance Service between 1 January 2010 and 31 December 2017, using International Classification of Diseases 10th revision diagnosis codes and information in the Rare In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The primary outcome of the study was newly diagnosed PD, which was identified by both ICD-19 code (G20) and registration code (V124) of the Rare Intractable Disease management program in Korea, as in prior studies [26][27][28]. Patients diagnosed with PD were identified with code V124, which is specified by criteria comparable to the UK Parkinson's Disease Society Brain Bank Diagnostic Criteria [29], and the diagnosis is confirmed by a neurologist or neurosurgeon.…”
Section: Study Outcome and Follow-upmentioning
confidence: 99%
“…The primary outcome of the study was newly diagnosed PD, which was identified by both ICD-19 code (G20) and registration code (V124) of the Rare Intractable Disease management program in Korea, as in prior studies [26][27][28]. Patients diagnosed with PD were identified with code V124, which is specified by criteria comparable to the UK Parkinson's Disease Society Brain Bank Diagnostic Criteria [29], and the diagnosis is confirmed by a neurologist or neurosurgeon.…”
Section: Study Outcome and Follow-upmentioning
confidence: 99%
“…This study was conducted as a retrospective matched cohort study from March 2022 to April 2023. 15 MS and NMOSD were defined as in a previous study in Korea and used the same database: [16][17][18] both ICD-10 diagnosis codes and information from the Rare Intractable Disease (RID) management program in South Korea, which has been operated since 2009, were used. Patients registered in the RID pay 10% of their total medical expenses out-of-pocket instead of the usual 20%-60% of total medical expenses.…”
Section: Definitions Of Ms/nmosd and Matched Controlsmentioning
confidence: 99%
“…MS and NMOSD patients met the following criteria: (1) ⩾2 outpatient or hospitalization claims with the relevant ICD-10 code (G35.0 for MS and G36.0 for NMOSD) and ( 2) registration in the RID system with the code (V022 for MS and V276 for NMOSD). 17 The index year for MS and NMOSD patients was designated as the year of the first claim for each case.…”
Section: Definitions Of Ms/nmosd and Matched Controlsmentioning
confidence: 99%
“…The RID program provides a copayment reduction of up to 10% for various rare and intractable diseases including ALS. 10 To be registered in the RID program, a diagnosis certification submitted by a neurologist is required based on the Awaji criteria or revised El Escorial criteria. A total of 2,252 ALS patients were identified according to the following criteria (Figure 1): (i) ≥2 outpatient or hospitalization claims with the ICD-10 code G12.21 for ALS and (ii) registration in the RID with code V123 for ALS.…”
Section: Study Participantsmentioning
confidence: 99%